2010
DOI: 10.1155/2010/487406
|View full text |Cite
|
Sign up to set email alerts
|

PECVD Silicon Nitride Passivation on Boron Emitter: The Analysis of Electrostatic Charge on the Interface Properties

Abstract: The dependence of surface recombination of boron diffused and undiffused silicon surfaces passivated with a-SiN x :H on the net charge density is investigated in detail. The films are deposited by plasma-enhanced chemical vapour deposition using a 2.45 GHz microwave remote plasma system. The surface charge density on the samples is varied by depositing charge using a corona discharge chamber. Excess carrier lifetime, capacitance-voltage, and Kelvin probe measurements are combined to determine the surface recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…Table summarises the Q eff and S eff.max data obtained for SiN x in this work compared with other remote plasma SiN x films. The Q eff of +8 × 10 12 cm −2 found in this work for nearly stoichiometric SiN x films is significantly higher than previously published values obtained for as‐deposited SiN x films using a similar PECVD reactor. Theoretically, it was shown that, for high charge densities (>5 × 10 11 cm −2 ), the surface recombination rate ( U ) is inversely proportional to the square of the fixed charge density ( Q f ), that is, U ≈ 1/| Q f | 2 .…”
Section: Resultscontrasting
confidence: 74%
“…Table summarises the Q eff and S eff.max data obtained for SiN x in this work compared with other remote plasma SiN x films. The Q eff of +8 × 10 12 cm −2 found in this work for nearly stoichiometric SiN x films is significantly higher than previously published values obtained for as‐deposited SiN x films using a similar PECVD reactor. Theoretically, it was shown that, for high charge densities (>5 × 10 11 cm −2 ), the surface recombination rate ( U ) is inversely proportional to the square of the fixed charge density ( Q f ), that is, U ≈ 1/| Q f | 2 .…”
Section: Resultscontrasting
confidence: 74%
“…The high temperature anneal results in a densification and modification of the electrical properties of the nitride film. This trend is also suspected to be the continuation of the trend observed during C-V measurement where anneal at 400°C resulted in a substantial reduction on hysteresis [8]. Hence, annealing 978-1-4244-5892-9/10/$26.00 ©201 0 IEEE at high temperature may cause further densification and increase in charge transfer barrier, causing the charge injection into and out of the film becomes more difficult.…”
Section: The Effect Of High Temperature Annealsupporting
confidence: 53%
“…(4) <eif <b W Negative charges were initially depOSited followed by charge removal in isopropyl alcohol (IPA) solution and deposition of positive charges. The starting point in each graph hereafter, prior to any charging, is given by Qf that is determined from CV measurements in the dark [8], while the applied surface charge density (from corona charging)…”
Section: Resultsmentioning
confidence: 99%
“…This is low compared to the samples Bonilla et al presented (Q f = + 2.2 × 10 12 and Q f = +2.6 × 10 12 cm −2 ), but in line with the work of Haug et al (Q f ≈ + 0.65 × 10 12 cm −2 ) and in general not uncommon for SiN x with x ≈ 1. 87,88 The pristine surface recombination velocity of our sample is S eff ≈ 53 cm s −1 . This is in the same order of magnitude as Bonilla et al and Haug et al presented.…”
Section: Journal Of Applied Physicsmentioning
confidence: 96%